International Children’s Rights (Human Rights – Children’s Rights, 2024)
The International Children’s Rights volume provides a comprehensive overview of the evolution, content, and implementation of international children’s rights law. Starting from the historical development of children’s rights and the legislative history of the UN Convention on the Rights of the Child, the book discusses the Convention’s key principles and its three main dimensions of protection, provision, and participation. It examines the role of the Committee on the Rights of the Child and the three Optional Protocols, as well as the contribution of national human rights institutions, UNICEF and non-governmental organisations to the implementation of the Convention. Further chapters address children’s rights in the context of the Sustainable Development Goals and in the practice of the International Criminal Court, offering readers an up-to-date and coherent picture of how international standards on children’s rights are interpreted and applied in theory and practice. This volume offers a clear and timely introduction to international children’s rights law within the ICCR sub-series, providing essential doctrinal and practical insights for scholars, practitioners, and students, particularly in Central Europe.